Relatório do estágio curricular supervisionado em medicina veterinária: área de clínica médica e cirúrgica de equinos - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The Supervised Curricular Internship in Veterinary Medicine (ECSMV) was conducted from April 22 to July 13, 2014, at Clínica Horse Center in Petrópolis, RJ, focusing on Equine Clinical Medicine and Surgery. The total workload was 480 hours, under the guidance of Prof. Dr. Cláudia Acosta Duarte and supervision of veterinarian Carlos Eduardo Martins de Oliveira Veiga. The student participated in routine care, emergencies, surgeries, diagnostic imaging, and other procedures, with the majority of cases involving musculoskeletal and digestive systems. This report details the activities performed and discusses four clinical cases: septic arthritis in a foal, osteochondritis dissecans, cecal impaction, and first phalanx fracture. The experience was essential for the practical consolidation of the knowledge acquired throughout the undergraduate program.
Report on the supervised curricular internship in veterinary medicine: area of ​​equine medical and surgical clinic
Keywords: Clínica e cirurgia de equinos; Estágio supervisionado; Medicina veterinária; Equine clinical and surgical medicine; Clinical cases; Veterinary medicine; Supervised internship; Casos clínicos; CNPQ::CIENCIAS AGRARIAS